Pembinaan Kesiswaan di SMK Negeri 2 Padang - Yufina Yenedi; Rifma Rifma; Ahmad Sabandi; Nelfia Adi (Journal of Educational Administration and Leadership, 2022)
This study aims to find out information related to student development at SMK Negeri 2 Padang. This type of research is descriptive research. This study uses descriptive statistical analysis techniques. The population in this study were all students of class X, XI and XII at SMKN 2 Padang with a total of 1,546 students and a sample of 130 students drawn from the population using the Slovin formula and the Stratified Proportional Random Sampling technique. The trial was conducted on 20 students outside the research sample. Test the validity and reliability using the IBM SPSS 24.0 for windows program. The validity test of this study used the product moment with a significant level of 5% (0.444) and the reliability test used the Alpha formula. The data is processed using the average formula (mean). The results of this study indicate that student development in aspects (1) fostering students' faith and devotion to God Almighty is in the good category with an average of 3.90; (2) the development of noble character or noble character of students is in the good category with an average of 4.15; and (3) the development of superior personality, national insight, and state defense of students is in the good category with an average of 4.13. Overall, it can be concluded that student development at SMK N 2 Padang is in the good category with an average score of 4.06.